Investigating the performance of cement mortar containing rice straw ash, microsilica and their composite by compressive strength - Pandey A.; Kumar B. (My University, 2025)
The primary objective of this research was to compare the effect of partial replacement of OPC with Rice straw ash, microsilica and their composite on the compressive strength of cement mortar. High range water reducer (HRWR) was also used to compensate for the decreased workability due to an increase in the overall surface area of the cementitious material. Its dosage for the different mix was decided by the Marsh Cone Test. Different proportion of rice straw ash and microsilica used for part replacement of OPC in the mortar were 5, 10, 15, 20, 25% and 2.5, 5, 7.5, 10% by weight of OPC respectively. The compressive strength of the mortar cubes of various proportions was determined after 3, 7, 28, 60, 90 and 365 days of curing in water. It was observed that the highest pozzolanic reaction could be achieved by mix R1M3 thus leading to increased compressive strength while the mix R2M3 could achieve both economy and relatively increased compressive strength. © BEIESP.